Modernization of Training Programs for Educational Institutions Heads on the Basis of Conceptual Foundations of Vocational Training for Manager Leaders - Калашнікова, Світлана Андріївна (Educological discourse, 2014)
The article presents the experience of modernization of educational institutions heads’ training programs carried out at Borys Grinchenko Kyiv University on the basis of implementation of conceptual foundations to vocational manager leaders’ training.